1997
DOI: 10.1038/sj.leu.2400840
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth of human leukemia cell lines by retrovirally expressed wild-type p16INK4A

Abstract: CDK6 activity.We tested the efficacy of our system by expressing the wt orEvidence from studies on both cell lines and human tumors deletion of the p16 gene, frequently point mutations are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Indeed, restoration of p16 expression in p16-deficient solid tumor cell lines or overexpression of p18 resulted in a dramatic reduction of growth and malignant phenotype. 18,130 To test the hypothesis that p16 suppresses the growth of p16 del leukemias, six studies utilized retroviral systems or electroporation to reestablish p16 wild-type expression (Table 8).…”
Section: Correlation Of P16 Deletions With Alterations Of P53 and Rb mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, restoration of p16 expression in p16-deficient solid tumor cell lines or overexpression of p18 resulted in a dramatic reduction of growth and malignant phenotype. 18,130 To test the hypothesis that p16 suppresses the growth of p16 del leukemias, six studies utilized retroviral systems or electroporation to reestablish p16 wild-type expression (Table 8).…”
Section: Correlation Of P16 Deletions With Alterations Of P53 and Rb mentioning
confidence: 99%
“…130 The inefficient inhibition of HL-60 proliferation post-p16 wt transfer remains unexplained. It should be noted that most studies reported a heterozygous p16 deletion for HL-60 accompanied by a p16 point mutation, whereas others did not find any p16 deletion in HL-60 at all.…”
Section: Tablementioning
confidence: 99%
“…Homozygous disruption of only the p19 ARF alleles with retained p16 INK4A alleles (p16 INK4A+/+ /p19 ARF7/7 ) also resulted in tumor formation including lymphomas; and tumors that developed in the heterozygous p19 ARF+/7 mice showed a loss of the wild type allele p19 ARF , suggesting a selective growth advantage for hematological malignancies which lose p19 ARF (Kamijo et al, 1997(Kamijo et al, , 1999 (Quesnel et al, 1996;Gombart et al, 1997;Lewis et al, 2001), CEM (Quesnel et al, 1996;Gombart et al, 1997), JURKAT (Quesnel et al, 1996), Granta 519 (Jadayel et al, 1997), NB4 (Gombart et al, 1997) or JKB (Urashima et al, 1997), their growth was retarded and they partially underwent di erentiation, suggesting that p16 INK4A -de®ciency might contribute to the malignant phenotype. No e ect of introduction of wild type p16 INK4A was observed in the p16 INK4A -de®cient HL-60 (Quesnel et al, 1996) and HSB-2 cells (Gombart et al, 1997), but HSB-2 cells also lack wild type Rb, a downstream target of p16 INK4A (Figure 1). Of future interest will be to express ectopically the wild type p14 ARF in cell lines with inactivated p16 INK4A /p14 ARF locus and wild type expression of p53, to determine whether reintroduction of p14 ARF will cause a growth inhibitory e ect either alone or in combination with p16 INK4A .…”
Section: Ink4 Family Of Proteinsmentioning
confidence: 99%
“…Expression of p16 was able to suppress the transformed phenotype of cells induced by H-Ras and CMyc, 77 and to produce G1 arrest in cell lines which retain functional pRb. 73,[78][79][80][81] The p16 shares a great deal of nucleotide sequence homology with p15, which was identified as an inhibitor induced by transforming growth factor-␤ (TGF-␤). 71 The p15 gene is localized 25 kb upstream of the p16 locus on chromosome 9p21.…”
Section: Cyclin-dependent Kinases (Cdkis) and Tumorigenesismentioning
confidence: 99%